Jenis-Jenis Carnivora di Kawasan Suaka Alam Malampah, Sumatera Barat, Indonesia - Nindy Ladyfandela; Wilson Novarino; Jabang Nurdin (Universitas Andalas, 2018)
An inventory of Carnivore species in Malampah Nature Reserve, West Sumatra had been conducted between Mei-August 2016. After a total of 303 trap nights, this study documented 19 species of mammals from 3 families of which 6 species from Carnivora. The documented carnivores were Catopuma temminckii (17 photos), Neofelis diardi (5 photos), Pardofelis marmorata (2 photos), Helarctos malayanus (3 photos), Paguma larvata (5 photos), and Prionodon linsang (1 photo). The finding on Carnivore was then discussed to highlight their implications for conservation.